Analisis Kelayakan Dalam Kajian Perspektif Keuangan Dan Analisis Sensitifitas (Studi Kasus Pada Pembangunan Hotel Teraskita Mataram) - Ignatius Joko Herwanto; Aloysius Harry Mukti; Edi Wahyu Wibowo (JURNAL ILMIAH BISNIS, PASAR MODAL DAN UMKM, 2021)
The research aims to analyze the feasibility study of Teraskita Hotel development that located in the branch office building of PT Waskita Karya at Mataram. The branch office building currently no longer in operation, so that Teraskita Hotel development could generate the advantageous value towards the company. Throughout the analysis of investment valuation, it could be seen that the whole aspect of the investment valuation such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP) and Profitability Index (PI) have appropriate result. However, the development plan of Teraskita Mataram Hotel is suitable to be realized. Related to the sensitivity analysis of the hotel room price, the study shows that if we scale down the room rate starting at 10% and above, or else loan interest is raised by 2% and above, and also the occupancy rate target in the first year is obtained up to 35%, whereas the necessary costs is fixed, it would affect the revenue to be decreased as well as the NPV value to negative and IRR value below WACC value so that the project development would not feasible to be implemented.